Solusi Penanganan Pembiayaan Bermasalah Di Bank Syariah Dalam Konteks Perundang-Undangan Republik Indonesia - Mochammad Afif (JES (Jurnal Ekonomi Syariah), 2018)
When the enactment of Act Number 7 of 1992 concerning banking there is another alternative form in addition to conventional banks that are known a bank based on the principle of profit sharing. Act Number 7 of 1992 concerning Banking has not yet used explicitly the term sharia bank or Islamic bank. The mention still uses the term “profit sharing principle”. There is no more detailed provision regarding banks conducting business based on sharia principles. Financing is the majority of assets of sharia banks so that the financing must be maintained with quality based on the principle of prudence. The precautionary principle is a bank management guideline that must be adopted in order to realize a sound, robust and efficient banking system in accordance with the provisions of laws and regulations. Implementation of prudential principles by sharia banks is one of which is realized in performing a financing analysis that is analyzing confidence on the willingness and ability of prospective customers of the facility receiver to repay all obligations in time, before the Sharia Bank and/or UUS channel funds to the facility receiver. This confidence is derived from a careful assessment of the time, ability, capital, collateral, and business prospects of a potential customer (character, capacity, capital, collateral, condition). The sharia bank in providing financing hopes that the financing proceeds smoothly, the customer obeys what has been agreed upon in the agreement and pays in full when it matures. However, it can occur within the financing period of non-performing financing. Efforts made by sharia bank to handle problematic financing by conducting a rescue of troubled financing with restructuring efforts if the customer still has good intentions in the sense of still willing to be invited to cooperate in efforts to save troubled financing, but if the customer has no conviction either in the sense cannot be invited in an effort to rescue non-performing financing, sharia banks will make efforts to settle non-performing financing. Keywords: Sharia Bank, Non Performing Financing, Handling Solution